Improved power losses calculation model for air core reactors - ZANINELLI, Henrique Borges (2021)
Air core reactors (ACR) have been widely used in power systems in several different applications like harmonic filters, thyristor-controlled reactors (TCR) for static var compensators (SVC), mechanically switched reactors (MSR) for shunt compensation of long transmission lines, smoothing and valve reactors for line commutate converter (LCC) and for voltage sourced converted (VSC), respectively, in HVDC systems, onshore and offshore. As a global trend, the pursuit of environmentally friendly equipment has increased, leveraging the use of ACRs in ultra-high voltage (UHV) systems. Applying that equipment in such voltage levels demands very accurate calculation models to establish the proper design parameters (e.g., inductance values, power losses and audible noise levels) as well as the stresses (dielectric, thermal and mechanical) that the equipment will have to withstand during operation, for their lifecycle. One typical concern related to those calculation models is regarding the prediction of the eddy current winding losses by analytical models. Several models have been proposed for this type of calculation for transformers and electrical machines, but usually with some constraints that make those models more suitable to that equipment than to others. With the crescent demand for ACR with lower power losses levels, it makes sense to look for improvements on those calculation models. One way of supporting the enhancement of those models is using software based on finite element methods (FEM) that allows for very detailed simulation of the physical phenomena related to the air core reactors and their applications. Although the FEM is a powerful tool for complex simulations, it is usually very time consuming and may require sophisticated computational apparatus to run more complex models. Air core reactors are equipment composed by one or several concentric windings made of conductive material (aluminum or copper) and their design may vary significantly, from a few kilograms to some dozens of tons. The simulation, in a reasonable time, of that equipment with several windings and sometimes thousands of turns would require computers that are not easily found in regular industries. In this work an optimized modeling process for simulating ACR using a 2-D equivalent geometry method in a finite element-based software was developed to allow for faster simulations. The validation of the method is performed by running a full factorial design of experiments (DOE), screening four design parameters of windings: winding diameter, winding height, number of strands and strand diameter, as these parameters significantly affect the two main design characteristics of the air core reactors: inductance and winding power losses. The results of the finite element simulations are statistically compared to the results of analytical calculations. With the deployment of this process, an improvement for the calculation of the eddy current winding losses of that equipment is proposed.